160 years of aggregate supply and demand in Switzerland - Rebecca Stuart (University of Neuchâtel, Institute of Economic Research (IRENE), 2022)
This paper studies the causes of movements in inflation and output in Switzerland over 160 years between 1855 and 2015. Aggregate supply and demand shocks are identified in a structural VAR and their evolution and effect on prices and output is discussed. Shocks to the Swiss economy have generally, although not uniformly, declined in magnitude over the sample period. The pre-Gold Standard era and the inter-war period were particularly volatile. Surprisingly, the global financial crisis represented a much smaller shock than either of the World Wars, the deflation of the 1920s, or the Great Depression.
Keywords: E1; E4; N1; 330; Switzerland; aggregate supply and demand; long time series; SVAR